Neuro Network Solution to the Design of a Hall Effect Current Transformer - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
Today, the Hall sensor based current measurement approach is being widely used as they have both AC and DC current measurement capability. Its most important application fields are current and power sensing, magnetic field sensing and distance sensing. Especially, it facilities the flux density sensing of the magnetic material inside for which the flux density measurement is very difficult. The relationship between input and output parameters (Primary MMF and measurement voltage) of The Hall Effect current transformer was examined and estimation of measurement voltage was carried out. The results show that the artificial neural network model produces reliable estimates of measurement voltage of a Hall Effect current transformer.
Keywords: Hall Effect; Current Sensing; Current Measurement; Hall Effect Current Transformer; Closed Loop Current Transformer; Artificial Neural Network